Evaluation of the Microorganisms in Nigeria Honey for Antagonistic Activity on Selected Bacteria causing Diarrhoea (Bangladesh Journal of Medical Science, 2022)
Objective: The aim of this study was to determine the antagonistic activities of the isolated microorganisms from honey on the selected diarrhoeagenic bacteria, for this reason the microbiological quality of Nigerian honey was investigated.Materials and Methods: Twelve (12) honey samples from different locations in Nigeria were evaluated and the microorganisms present in those samples were studied and isolated. Both clinical and typed cultures of Escherichia coli, Salmonella typhimurium, Shigella dysenteriae, Bacillus cereus and Staphylococcus aureus were also used for the study.Results: A total of 9 bacterial and 8 fungal species were isolated from the honey samples: Bacillus proteolyticus, Providencia rettgeri, Lysinibacillus pakiestanensis, Bacillus thuringiensis, Acinetobacter indicus, Bacillus cereus, Bacillus subtilis, Lysinibacillus fusiforms, Bacillus amyloliquefaciens and Aspergillus flavus, Penicillium chrysogenum, Neurospora crassa, Rhizopus stolonifer, Fusarium oxysporum, Mucor racemosus, Trichodermaviride, Saccharomyces cerevisae respectively. Among the 9 bacteria isolated, 4 (44.44%) exerted antagonistic effect on 6 (60%) of thetest bacteria. On the other hand, 2 (25.00%)among the 8 fungi isolated had antagonistic activity against 4 (40.00%) of the test bacteria.Conclusion: However, honey has anti-microbial properties that discourage the growth or persistence of many microorganisms which made them to contain low numbers and a limited variety of microbes. The bacteria isolated exerted a greater antagonistic activity than the isolated fungi on selected diarrhoeagenic bacteria, which could have been as a result of secondary metabolites like lipopeptides, polypeptides, fatty acids, isocoumarins produced by them that exhibited a wide range of biological activities such as antimicrobial.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 553-561